A clinical and radiographic study of four different root canal fillings in primary molars - Alaa O Al-Ostwani; Bashier M Al-Monaqel; Mohamed K Al-Tinawi (Wolters Kluwer Medknow Publications, 2016)
Background: Successful treatment of infected primary teeth aims to preserve the child's health. However, the complex morphology of primary root canals and the desire for shorter therapy sessions put the necessity to search for the ideal root canal paste. Aims: To evaluate pulpectomy of nonvital primary molars using four different root canal filling pastes zinc oxide and propolis (ZOP) as a new paste, endoflas-chlorophenol-free as a new paste free of chlorophenol, metapex paste, and zinc oxide and eugenol (ZOE) paste as a control paste. Materials and Methods: Pulpectomy of 64 nonvital primary molars were accomplished in 39 children aged 3-9 years. Teeth were randomly divided into four equal groups of 16 molars according to the type of root canal filling. Pulpectomy was performed in one stage using 5.25% sodium hypochlorite irrigation and stainless-steel crown for final restoration. Clinical and radiographic results were evaluated double-blindly for two periods of 6, 12 months. Data were analyzed using Chi-square/Fisher's exact test, and P-value was set as 0.05. Results: The four pastes achieved convergent clinical and radiographic success within the two observation periods (P > 0.05). ZOE paste was the slowest in its resorption. Conclusions: ZOP is a promising paste with its natural antibacterial component (propolis). ZOE paste had convergent efficacy to the other pastes.